Optimasi Konsentrasi Air Kelapa Muda terhadap Morfogenesis dan Efisiensi Multiplikasi Planlet Kentang (Solanum tuberosum L.) Kultivar Granola pada Media Murashige dan Skoog - Muhammad Fadli Ramadhan; Nur Aisyah Putri (Lembaga Publikasi Ilmiah Nusantara, 2026)
Granola potato (Solanum tuberosum L.) is a strategic horticultural crop in Indonesia, and its productivity largely depends on the availability of high-quality planting materials. In vitro tissue culture through shoot multiplication is an effective approach for the mass propagation of disease-free seedlings. Young coconut water contains natural cytokinins, auxins, gibberellins, amino acids, and minerals that have the potential to replace or enhance synthetic plant growth regulators in Murashige and Skoog (MS) medium. This study aimed to evaluate the effects of different concentrations of young coconut water on the morphogenesis of Granola potato plantlets, identify the optimum concentration for efficient shoot multiplication, and generate quantitative data on in vitro plantlet growth. The experiment was arranged in a completely randomized design with five concentrations of young coconut water (0, 50, 100, 150, and 200 mL/L) and four replications. The observed parameters included the number of shoots, plantlet height, number of nodes, number of leaves, and percentage of rooted explants. The results showed that supplementation with 100 mL/L of young coconut water produced the best morphogenetic response, with an average of 4.85 shoots per explant, a plantlet height of 6.42 cm, and 91.25% rooted explants. Concentrations above 150 mL/L tended to inhibit plantlet growth. The findings demonstrate that young coconut water at an optimum concentration is an effective natural source of cytokinins for supporting the in vitro multiplication of Granola potato plantlets.